The diagnostic value of interleukin 35 as a septic biomarker: A meta-analysis - hu, yuanhui; tang, dongling; zhang, pingan (Frontiers in Medicine, 2022)
Background: There is growing evidence that interleukin 35 (IL-35) represents a potential diagnostic biomarker for sepsis. The purpose of this meta-analysis was to evaluate the overall diagnostic accuracy of IL-35 in sepsis. Methods: From October 1998 to May 2022, set retrieval standards were used to search literature Databases. Each included study was assessed diagnostic accuracy study quality assessment tool. Two researchers independently extracted the data and research features. If there are differences, the issue will be resolved by mutual agreement. Meta-disc and Stata software were utilized to calculate combined sensitivity, specificity, and summary diagnostic odds ratio (SDOR), I², or Cochrane Q in order to detection for heterogeneity, and meta-regression was performed to figure out the cause of heterogeneity. Utilizing funnel plots, we tested for publication bias. Results: In this meta-analysis, eight publications were included. The combined sensitivity, specificity, and DOR were 0.87 (95% CI, 0.77- 0.93), 0.73 (95% CI, 0.60- 0.83), and 18 (95% CI, 10- 34), respectively. In addition, 0.88 (95% CI, 0.84-0.90) was the area under the summary receiver operating characteristic curve. In the heterogeneity analysis, the sensitivity of comprehensive I2 statistic was 84.38, and the specificity was 87.82. Deeks’ funnel plot showed no publication bias in this meta-analysis (P = 0.17). A meta-analysis revealed that IL-35 has a modest sensitivity (AUC=0.88) for diagnosing sepsis. Conclusions: IL-35 is a valuable biomarker for the early detection of sepsis. However, the data should be combined with clinical symptoms, signs, laboratory and microbiological findings.